2020
DOI: 10.1111/jonm.13211
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Turkish version of the General Work Stress Scale

Abstract: Aim To test the validity and reliability of the Turkish version of the General Work Stress Scale. Background Nursing is one of the most stressful professions. The primary measure that should be taken to ensure that nurses can cope with stress is determining their stress levels. Method The General Work Stress Scale was translated into Turkish via back‐translation. Its reliability and validity were analysed via item analyses, content and construct validities, exploratory and confirmatory factor analyses, Cronbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…High scores indicate high work stress whereas low scores indicate low work stress. The Turkish validity and reliability study was performed by Teles and the Cronbach α value of the scale was found 0.91 (Teles, 2021 ). In this study, the Cronbach α value was determined as 0.93.…”
Section: Methodsmentioning
confidence: 99%
“…High scores indicate high work stress whereas low scores indicate low work stress. The Turkish validity and reliability study was performed by Teles and the Cronbach α value of the scale was found 0.91 (Teles, 2021 ). In this study, the Cronbach α value was determined as 0.93.…”
Section: Methodsmentioning
confidence: 99%
“…High scores imply a high level of job stress, whereas low scores denote a low level of work stress. According to Teles' validity and reliability analysis of the scale in Turkey, the scale's Cronbach alpha score is 0.91 [33]. The Cronbach alpha value for this study was found to be 0.92.…”
Section: Measurementsmentioning
confidence: 61%
“…“Does work make you so stressed that you wish you had a different job?” and “Does work make you so stressed that you find it hard to concentrate on your tasks?”) was developed by De Bruin (2006) . Teleş (2021 , p.716) conducted a validity and reliability study of its Turkish version. The Cronbach's alpha coefficient was 0.91 for its Turkish version, meaning that this scale has high reliability.…”
Section: Methodsmentioning
confidence: 99%